RESPON PEMBERIAN PUPUK ORGANIK CAIR KULIT PISANG DAN Mucuna bracteata TERHADAP PERTUMBUHAN TANAMAN BAYAM MERAH (Amaranthus tricolor L.) - Yudi Triyanto (JURNAL AGROPLASMA, 2019)
Waste banana peels are not experiencing good management would cause environmental pollution. Sewage still contains high water content and contains organic materials in the form of carbohydrates, proteins, and fats. One of the ways that can be done to manage the industrial waste is to turn it into liquid compost (organic liquid fertilizer) fertilizer because liquid organic more quickly seeped into the ground and was quickly utilized directly by plants, and do not damage the soil and plants. This research aims to produce liquid organic fertilizer made of waste banana peels and Mucuna bracteata and know response granting POC banana peels and Mucuna bracteata against red spinach plant growth (Amaranthus tricolor L.). The research design used was randomized factorial (RAK) group with 1 factors and five levels of treatment: C0: 0 ml/plant, C1: 20 mL/plant, C2: 40 mL/plant, C3: 60 mL/plant, C4: 80 ml/plant, and continued with the test Duncan's Multiple Range tests. The parameters observed were higher plants (cm), number of leaves (strands), diameter clump (cm). The grant of a liquid organic fertilizer (POC) waste banana peels and Mucuna bracteata influential real high against the plant, number of leaves, and the diameter of the clump. Keywords: Waste banana peels, liquid organic fertilizers, growth of red spinach